A New Caffeine Test for Diagnosis of Cirrhosis by GC/MS - Mesaros, C.; Culea, M.; Iordache, A.M.; Visovan, I.; Cozar, C.; Cosma, C. (Asian Journal of Chemistry, 2010)
A method for caffeine levels determination in children suffering from liver diseases by gas chromatography-mass spectrometry (GC/MS) is presented. The selected ion monitoring (SIM) mode was used in caffeine test measurements by adding known amounts of the 15N labelled internal standard. The method was validated in the range 0-20 μg/mL caffeine. A single dose of 4 mg/kg p.o. of caffeine was followed by blood concentrations measurements at two points, 1 and 9 h. Caffeine clearance, 0.74 ± 0.49 mL min-1 kg-1, measured in patients with cirrhosis was reduced and half live time, t1/2 = 14.73 ± 12.36 h, was increased as compared with controls of 1.28 ± 0.31 mL min-1 kg-1 and t1/2 = 5.73 ± 1.58 h.